"A Comparıson Of Soft Tıssue Profıle Confıguratıon In Deep Overbıte And Normal Occlusıon Cases" - Murat Özbek; Haluk İşeri (Galenos Yayinevi, 1994)
Soft tissue profile characteristics of 57 subjects (28 boys and 29 girls) with deep overbite and Angle Class I or Class II division 2 relationship were compared with those of 65 subjeects (34 boys and 31 girls) exhibiting an esthetically pleasing soft tissue profile and normal Class I occlusion. Student-t test was used for the comparison of groups, whereas the associations between soft tissue profile and dento-skeletal variables were evaluated by means of Pearson"s r correlation coefficients. Regarding the most apparent common soft tissue characteristics of subjects from both sexes with deep overbites; an increase in the discrepancy between the sagittal lip relation due to a more posterior positioning of the lower lip; an increase in sublabial cun'ature angle and a decrease of lower lip vertical height were obsen'ed. A "dished-in" profile was not found to be a characteristic of deepbite for girls, whereas the differences between normal and deep overbite groups were statistically significant for boys. Results of the correlation analysis revealed that the soft tissue differences between groups were merely due to the dentoalveolar factors, rather than the skeletal variables, except those indicating the lower facial height and the sagittal mandibular position.